THE EFFECTIVENESS OF INTERACTIVE WRITING TECHNIQUEIN IMPROVING STUDENTS' WRITING ABILITY(AN EXPERIMENTAL STUDY OF ELEVENTH GRADE AT A SENIOR HIGH SCHOOL IN GARUT) - Eva Agustin Muthmainnah, - (2009)
This paper is entitled "The Effectiveness of Interactive Writing Technique in Improving Students' Writing Ability". This research was aimed to investigate the effectiveness of the interactive writing technique in writing especially in revising stage and to figure out the students' responses toward the technique. The method used in this study was quasi experimental with quantitative approach. The research was conducted at Madrasah Aliyah PPI 76 Garut. The students who participated in this research were XI Sains 2 and XI Sains 1. The pre-test and post-test were analyzed to investigate the effectiveness of the technique. Meanwhile the questionnaire was distributed to figure out the students' responses toward the technique in experimental class only. The post-test data indicate that there were differences between means of experimental group and control group. It was supported by the t-test computation in which the result shows that the null hypothesis is rejected and the alternative hypothesis accepted. Moreover, the questionnaire result displays that almost students show positive response toward the interactive writing technique. It can be concluded that the interactive writing technique is expected to be the effective way in improving students' writing ability.